2007
DOI: 10.1016/j.brainres.2006.10.047
|View full text |Cite
|
Sign up to set email alerts
|

An analog of thyrotropin-releasing hormone (TRH) is neuroprotective against glutamate-induced toxicity in fetal rat hippocampal neurons in vitro

Abstract: TRH has been found to be efficacious in treating certain neurodegenerative disorders such as epilepsy, Alzheimer's disease, neurotrauma and depression, however, its mechanism of action is poorly understood. Since Glutamate (Glu) toxicity has been implicated in these disorders, we utilized primary enriched cultures of rat fetal (E 17) hippocampal neurons to test the hypothesis that an analog of TRH, 3-Methyl-Histidine TRH (3Me-H TRH), given concurrently with Glu would protect such neurons against cell damage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…The ancestral role of TRH as a neuroregulator is being increasingly recognized and an analog has been successfully used in vitro as a neuroprotective agent in the glutamateinduced toxicity that is associated with neurodegenerative diseases such as Alzheimer's [101].…”
Section: Tertiary Effects On the Thyroid Systemmentioning
confidence: 99%
“…The ancestral role of TRH as a neuroregulator is being increasingly recognized and an analog has been successfully used in vitro as a neuroprotective agent in the glutamateinduced toxicity that is associated with neurodegenerative diseases such as Alzheimer's [101].…”
Section: Tertiary Effects On the Thyroid Systemmentioning
confidence: 99%
“…TRH analog ligands can also exert protective effects against Aβ toxicity in neuronal cell culture (Faden et al, 2005), reduce inflammatory cytokines TNF-α and IL-6 and attenuate lipid peroxidation, all of which have been implicated in oxidative stress and the predisposition for AD (Rajput et al, 2011). The TRH analog, 3-methyl-histidine-TRH, has also been shown to functionally antagonize glutamate-mediated neurotoxicity in fetal neurons in a concentration-dependent manner (Veronesi et al, 2007). Administration of L-T 4 in mice injected intrahippocampally with aggregated Aβ was shown to prevent cognitive impairment and improve memory function (Fu et al, 2010).…”
Section: The Potential Role Of Trh In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Its mechanism of action is poorly understood; however, it seems to be implicated in a protection against neuronal overexcitability. In fact, some authors reported that TRH could inhibit the effects of the glutamate-induced toxicity, in a dose-dependent manner, in cultured fetal rat hippocampal neurons (Pizzi et al, 1999;Veronesi et al, 2007). Furthermore, a paradoxical secretary peak of GH to TRH is more frequent during a status epilepticus.…”
Section: Thyrotropin-releasing Hormonementioning
confidence: 99%